Clinicopathological Characteristics of Basal Cell Carcinoma of the Head and Neck in Tertiary Care Hospital in Rawalpindi, Pakistan (Medical Forum Monthly, 2020)
Objective: Clinicopathological Characteristics of Basal Cell Carcinoma of the Head and Neck in Tertiary Care Hospital in Rawalpindi, Pakistan.Study Design: Randomized control trial study.Place and Duration of Study: This study was conducted at the Armed Forces Institute of Pathology, Rawalpindi (AFIP) from January 2016 to June 2016.Materials and Methods: Clinicopathological analysis is done using H and E staining technique. A sample of 114 patients were selected. Cases were recuperated from the Data on age, gender, location of tumor and histopathological variant was collected and analyzed using SPSS version.Results: BCC is common in males above 50 years of age comprising M: F ratio of 2.5:1 with nose been the most common anatomical site followed by the eye. Most common histopathological subtype include nodular variant followed by adenoid variant.Conclusion: Nose been the most common clinical site instituted along with nodular variant as most common histopathological subtype of BCC in head and neck region.